Inheritance of real estate under conditions of cohabitation - Pushka D. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the article is to explore the peculiarities of inheritance of real estate under conditions of joint residence, find out the legal consequences of the indissoluble marriage of the testator with a third person for the circle of heirs and determine their shares in the inheritance. The research methodology consists in the analysis of the provisions of the current legislation, the practice of their application and scientific doctrines. The research results revealed that joint residence can significantly affect the circle of heirs and their shares in the inheritance. In particular, the study showed that in the case of the indissoluble marriage of the testator with a third person, this person may have the right to a share in the inheritance, even if it has not been officially recognized heir. This can lead to difficulties in the section of the hereditary property between other heirs. Originality. The scientific novelty lies in a comprehensive analysis of the legal consequences of cohabitation on the inheritance of real estate under the conditions of the indissoluble marriage of the testator, which allows us to better understand the problems of the legal status of such heirs. Practical significance – providing recommendations on taking into account the issues of joint residence in the inheritance of real estate. It is necessary to pay attention to the relationship of formal legal requirements and principles of justice in determining the circle of heirs and the volume of their shares in the inheritance. The study of judicial practice in such hereditary disputes will reveal problematic aspects in the application of current legislation and formulate reasonable proposals for its improvement. The results of the study can be used to improve regulatory regulation in the field of inheritance in order to achieve a balance between compliance with formal requirements and ensuring fairness.